An alternative storage method for characterization of the intestinal microbiota through next generation sequencing - Ribeiro, Roberto Marques; Souza-Basqueira, Marcela de; Oliveira, Léa Campos de; Salles, Flavia Cristina; Pereira, Natalia Bueno; Sabino, Ester Cerdeira (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Gut microbiota has been the subject of various molecular studies mainly due to its importance and wide-ranging relationships with human hosts. However, the storage of fecal samples prior to DNA extraction is critical when characterizing the composition of intestinal microbiota. Therefore, we aimed to understand the effects of different fecal storage methods to characterize intestinal microbiota using Next Generation Sequencing (NGS) as well as to establish an alternative conservation method of bacterial genetic material in these samples using guanidine. Stool samples from 10 healthy volunteers were collected. Each sample was divided into five aliquots: one aliquot was extracted immediately after collection (fresh) and two aliquots were subjected to freezing at -20 °C or -80 °C and extracted after 48 h. The other two aliquots were stored in guanidine at room temperature or 4 °C and extracted after 48 h. The V4 hypervariable regions of the bacterial and archeal 16S rRNA gene were amplified by PCR and sequenced using an Ion Torrent PGM platform for NGS. The data were analyzed using QIIME software. Statistical significance was determined using a nonparametric Kruskal-Wallis test. A total of 11,494,688 reads with acceptable quality were obtained. Unweighted principal coordinate analysis (PCoA) revealed that the samples were clustered based on the host rather than by the storage group. At the phylum and genus levels, we observed statistically significant differences between two genera, Proteobacteria (p=0.013) and Suterella (p=0.004), comparing frozen samples with guanidine-stored samples. Our data suggest that the use of guanidine can preserve bacterial genetic materials as well as freezing, providing additional conveniences